A new infrageneric classification for Amorimia (Malpighiaceae) based on morphological, phytochemical and molecular evidence - de Almeida, Rafael Felipe; Amorim, André Márcio; Corrêa, Angela Maria Da Silva; van Den Berg, Cássio (Phytotaxa, 2017)
Phylogenetic relationships for 14 of the 15 species of Amorimia (Malpighiaceae) were inferred based on ndhF plastid DNA and ETS nuclear ribosomal DNA using both parsimony and Bayesian methods. Our results show that: (1) the monophyly of the genus is corroborated with the new circumscription of the A. rigida complex; (2) several morphological and phytochemical characters support Amorimia and its two main clades; and (3) these clades can be proposed as new subgenera in Amorimia.